Enhancing 21st century collaboration skills in physical education through the problem-based learning model - Rahmadi; Hardinata, Riyan; Ahwan, M. Tami Rosadi; Rubiyatno; Suryadi, Didi (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
Collaboration skills are pivotal for students, offering avenues to enhance knowledge, social interaction, self-confidence, and motivation. This study aims to enhance collaboration skills among students in physical education, particularly in the design of systematic rhythmic movement activities using the problem-based learning model. Conducted as classroom action research, the participants were 35 Class XI students from Public Senior High School 3 Banjarbaru. The research utilised a collaborative observation sheet and employed both descriptive and quantitative analysis methods. The results revealed a discernible improvement in collaboration skills between the initial and subsequent cycles. ANOVA tests demonstrated a significant increase after two cycles of learning. This research directly influences the development of collaborative abilities in learners, recognising collaboration skills as crucial in 21st-century education. The collaborative problem-solving approach not only enhances cooperation but also contributes to improved learning outcomes, preparing students for success in both community and work environments. The study sheds light on the efficacy of problem-based learning models, underscoring their vital role in learner development and education. Future research should explore the impact of problem-based learning models using mixed-methods research.